Efek Suplementasi Daun Ubi Kayu terhadap Kecernaan Daun Sawit Amoniasi secara In Vitro - - Nurhaita; R.W.S. Ningrat (Jurnal Peternakan Indonesia (Indonesian Journal of Animal Science), 2011)
The purpose of this study was to obtain the level of supplementation of cassava leaves as a source of branched chain amino acids in improving nutrients digestibility of ammoniation palm leaf, and characteristics of rumen fluid ( in-vitro). The experiment was designed by using randomized block design with 6 treatments of supplementation of cassava leaf (A = 0% as control, B = 5%, C = 10%, D = 15%, E = 20% and F = 25% of dry matter) with 4 replications. Parameters were: 1) Digestibility of nutrients (dry matter, organic matter, crude protein) 2) Digestibility of fiber fractions (NDF, ADF, cellulose and hemicellulose) and 3) Characteristics of rumen fluid (pH, NH3, and VFA) by in- vitro. The results showed cassava leaves supplementation significantly (P <0.05) increased the in-vitro digestibility of palm leaves ammoniation. The highest dry matter digestibility obtained at cassava leaf 5% (24.09%) in comparing controls (45.49% vs. 56.45%), and ADF digestibility increased by 36.91% compared to controls (37.25% vs. 51.00%). Cassava leaves maintained rumen fluid characteristics for microbial rumen growth and activities. It concluded, the level of supplementation cassava leaves as a source of the best branched chain amino acids in palm leaf ammoniation was 5%.